El linfocele en el trasplante renal. - Corral Rosillo, J.; Delgado Martín, J.A.; Mohamed Mohamed-abdallah, Z.; Resel, Luis; Gómez Vegas, Ángel; Peña Zarzuelo, E. De la; Silmi Moyano, A.; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1999)
Sin resumen